(untitled) (Journal of Humanitarian and Applied Sciences, 2026)
Examining the concept of focalization and its applications to Libyan folk proverbs reveals the eloquence of condensation and brevity. Folk proverbs possess the remarkable ability to compress a complete narrative text—encompassing characters, conflict, perspective, temporal and spatial dimensions, and outcomes—into concise expressions and a limited number of words that may not even constitute a full line of text. This characteristic makes them a fertile ground for the analysis of micro-narrative structures. The technique of focalization can therefore be employed in analyzing the narrative content of Libyan folk proverbs to demonstrate that a proverb is not merely a linguistic text. Such a reductionist view obscures its true nature as a cultural event and an integrated narrative structure. Focalization functions as a visual and interpretive strategy through which the distance between the listener and the narrated situation is determined. In this sense, it serves as a compass for the recipient, guiding their position in relation to the event—whether from within, outside, or above it—and thereby facilitating a deeper understanding of the intended wisdom and meaning embedded in the proverb.